Comparison of p53 immunohistochemical staining in differentiated vulvar intraepithelial neoplasia (dVIN) with that in inflammatory dermatoses and benign squamous lesions in the vulva. Issue 3 (27th October 2020) - Liu, Y Ariel; Ji, Jennifer X; Almadani, Noorah; Crawford, Richard I; Gilks, C Blake; Kinloch, Mary; Hoang, Lien
Abstract : Aims: Differentiated vulvar intraepithelial neoplasia (dVIN), the precursor lesion to human papillomavirus‐independent vulvar squamous cell carcinoma (VSCC), can be difficult to distinguish from vulvar inflammatory dermatoses. Our goal was to determine if p53 could be a useful biomarker for dVIN, by characterizing p53 percentage, intensity and patterns of staining in dVIN and its histological mimics. Methods and results: We studied p53 immunohistochemical staining patterns in 16 dVIN cases and 46 vulvar non‐neoplastic squamous lesions [12 lichen sclerosus (LS); seven lichen simplex chronicus; three lichen planus (LP); six psoriasis; 13 spongiotic dermatitis (SPO); and five candidiasis]. dVIN cases were adjacent to a p16‐negative invasive VSCC in resection specimens. All dVIN cases showed null‐type or moderate to strong uniform p53 staining in >70% of basal cells, with moderate to strong continuous parabasal staining extending to two‐thirds of the epidermis. This was in contrast to weak or weak to moderate patchy p53 staining in the majority of other lesions. Moderate to strong and increased basal p53 staining (≥70%) was also observed in a subset of LS cases (5/12, 42%), LP cases (1/3, 33%), and SPO cases (36%, 4/11); however, in all categories, this was limited to the basal layer, and any staining in the parabasal layers was patchy. Conclusion: Strong and uniform p53 staining of basal cells, extending into the parabasal layers, and a complete absence of staining (null type) is useful in distinguishing dVIN from other mimics in the vulva. p53 staining of lesser intensity or quantity, particularly basal overexpression only, overlaps with that in vulvar inflammatory lesions.